REKONSTRUKSI DESAIN INSTRUKSIONAL PAI BERBASIS MODEL ASSURE DAN DEEP LEARNING PADA MATERI MODERASI BERAGAMA - Siti Nafilatul Munawwaroh; Irma Soraya (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to reconstruct the Islamic Education (PAI) instructional design by integrating the ASSURE model with a Deep Learning approach to strengthen religious moderation values in the digital era. This research is driven by the increasing challenge of digital radicalization, which necessitates more sophisticated pedagogical responses beyond conventional teaching methods. Using a qualitative case study at SMAN 3 Sidoarjo, data were gathered through technical triangulation, including document analysis of teaching modules, participatory observation, and in-depth interviews. Findings reveal that the existing instructional design is predominantly procedural-administrative, making it suboptimal for internalizing affective values. Through data triangulation and structural gap analysis, this study formulates a practical integration matrix schema. The proposed reconstruction integrates the pillars of Mindful, Meaningful, and Joyful into the ASSURE stages, shifting the learning orientation toward a more contemplative process that fosters critical tabayyun (verification) behavior among students. The results imply that this reconstruction significantly deepens the internalization of tawasut (moderate) values by aligning learning experiences with students’ digital realities, while noting limitations in teachers' digital literacy and time constraints. Furthermore, this study contributes a new conceptual framework for technology-based character education that prioritizes spiritual and emotional depth. This study concludes that a Deep Learning-based instructional design effectively fosters inclusive, critical, and tolerant student characters.